Present and future accelerator options beyond the LHC. Issue 1 (19th November 2015) - Ferrario, Massimo
Abstract : Particle accelerators have been extraordinary discovery tools since the beginning of particle physics exploration. But accelerator's sizes and costs have now reached a critical limit, while the particle physics experiments require always higher energies. Is it time for a revolution in accelerator techniques or we can still rely in conventional methods? The next generation of discovery machines is presented together with the research on going in novel acceleration techniques. Picture: Courtesy of Deutsches Elektronen‐Synchrotron (DESY) ‒ TESLA Technical Design Report, DESY 2001‐011 Abstract : In this paper the present and future landscape of accelerators dedicated to fundamental science is reviewed. The current plans for future large facilities worldwide are discussed and the key performance parameters of the future machines as presently foreseen are given. New ideas and concepts that may bring more powerful machines for particle physics in the more distant future are also presented.